Citizenship Project as a Collaborative-Participatory Learning Model in the Learning of Civics Education Courses in Higher Education - Hanafi, Hanafi; Wafa, Alfian Fawaidil; Fattah, Zulfikar Waliyuddin (International Journal of Business, Law, and Education, 2025)
This study aims to provide an overview of the syntax (learning stages) and explore the advantages of the citizenship project learning model as a means to enhance students’ collaborative spirit and participation in implementing the theoretical substance of learning in Civic Education courses at universities. This learning model prioritizes students to be able to apply their knowledge, attitudes, and skills in real life through direct involvement in community, national, and state life. The benefits of this research can be used as a learning tool that can prioritize and hone critical thinking skills, find alternative solutions, so that it is hoped that they can solve problems in a collaborative-participatory manner in the context of citizenship. This research is a qualitative study using descriptive research. Data collection techniques were carried out through observation, interview, and documentation. The data analysis technique used refers to the qualitative data analysis approach of Miles and Huberman model which includes data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that the collaborative-participatory learning model through the implementation of citizenship projects in learning civics courses in higher education is very relevant for students who are able to increase the spirit of collaboration and participation through direct involvement of students in real situations and are able to accommodate students’ knowledge, understanding, attitudes and skills to be more useful for social, national and state life in the context of citizenship